2013
DOI: 10.1039/c3ay40715b
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of selective analyses of HDL and LDL cholesterol in clinical and point of care testing

Abstract: Cardiovascular disease is a leading cause of death worldwide and is caused by the build up of atherosclerotic plaques in the vasculature. It is now well established that the formation of these plaques is closely related to levels of both high density lipoprotein (HDL) and low density lipoprotein (LDL) cholesterol. Thus, the importance of the effective measurement of these is critical for the improved diagnosis and management of atherosclerosis. This review discusses the emergence of methodologies for the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…35 Non-HDL-C is considered to be atherogenic and so is better than the separate measurement of LDL-C. 36 …”
Section: Resultsmentioning
confidence: 99%
“…35 Non-HDL-C is considered to be atherogenic and so is better than the separate measurement of LDL-C. 36 …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many POCT biomedical diagnostic frameworks have been proposed [7]- [17]. Various POCT devices for both professional and consumer cholesterol measurements are available [18], [19]. For example, Cardiocheck PA detects the HDL results depending on a spectrophotometric strategy to mark the color change of the reflected light off an expendable test strip after applying blood test.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease is the number one cause of death in all developed countries. Several studies have demonstrated the increased risk of cardiovascular diseases including arteriosclerosis is strongly correlated with high cholesterol (CHO) levels (Ahmadraji and Killard, 2013). Thus, the determination of CHO levels in food and blood has been increasingly important for clinical analysis/diagnosis.…”
Section: Introductionmentioning
confidence: 99%